Kebijakan Pemerintah Dalam Mengakomodir Pendidikan Berbasis Kearifan Lokal di Indonesia - Haryanto, Iwan; Safitri, Ade; Sulindra, I Gusti Made (Jurnal Literasi dan Pembelajaran Indonesia, 2022)
Indonesia is a country that is rich in culture, customs, religion, and habits that grow, develop, and be preserved in the lives of our people. Through the preservation process, it is not only built in the community but also occurs in educational practice, both formal and non-formal education. This phenomenon certainly raises several questions, the first is what is the form of education based on local wisdom? And second, how is the government's policy in an effort to accommodate education based on local wisdom? This study uses a literature study whose findings come from research results and other library materials and then analyzed using qualitative analysis. So it was found that education based on local wisdom is education that comes from human potential, religious potential, cultural potential, and natural potential which are indirectly and unplanned actualized in the form of education in schools. In this education accommodation, through government policies, namely through the 1945 Constitution and Law Number 20 of 2003 concerning the National Education System.